Healthy eating in times of Covid-19: an integrative (Research, Society and Development, 2022)
This article aimed to analyze and highlight the importance of healthy eating in the midst of the COVID-19 pandemic, through a literary review, seeking to emphasize food care for health promotion and prevention and maintenance. For the selection of the sample, criteria were defined for articles indexed from 2011 to 2021 published in national and international journals. Data collection was carried out in the SCIELO, Pubmed and Google academic database using the following descriptors: Food, Covid-19, Immunity. The search resulted in 15 articles and after using the inclusion and exclusion criteria, 10 articles remained for analysis, interpretation and discussion. It was observed that there are many factors that can influence our immunity such as sleep, physical activity, emotional factors and food. Micronutrients play vital roles in the immune system, with vitamins A, C, D, B-complex, beta-carotene, iron, selenium and zinc being the most needed to support immunocompetence. The immune response is compromised when the nutritional status is inadequate, predisposing individuals to infections. It is concluded that although the new coronavirus pandemic brings several problems, it is necessary to emphasize that patients suspected or positive for covid-19 should receive all the necessary nutritional support.